Recombination and population structure in Salmonella enterica. - Xavier Didelot; Rory Bowden; Teresa Street; Tanya Golubchik; Chris Spencer; Gil McVean; Vartul Sangal; Muna F Anjum; Mark Achtman; Daniel Falush; Peter Donnelly (PLoS Genetics)
Salmonella enterica is a bacterial pathogen that causes enteric fever and gastroenteritis in humans and animals. Although its population structure was long described as clonal, based on high linkage disequilibrium between loci typed by enzyme electrophoresis, recent examination of gene sequences has revealed that recombination plays an important evolutionary role. We sequenced around 10% of the core genome of 114 isolates of enterica using a resequencing microarray. Application of two different analysis methods (Structure and ClonalFrame) to our genomic data allowed us to define five clear lineages within S. enterica subspecies enterica, one of which is five times older than the other four and two thirds of the age of the whole subspecies. We show that some of these lineages display more evidence of recombination than others. We also demonstrate that some level of sexual isolation exists between the lineages, so that recombination has occurred predominantly between members of the same lineage. This pattern of recombination is compatible with expectations from the previously described ecological structuring of the enterica population as well as mechanistic barriers to recombination observed in laboratory experiments. In spite of their relatively low level of genetic differentiation, these lineages might therefore represent incipient species.